Teknologi umpan berbahan aktif kitosan untuk pengelolaan rayap tanah Cototermes curvignathus Holmgren (Isoptera: Rhinotermitidae) - Arinana Arinana (Jurnal Ilmu Pertanian Indonesia, 2007)
The cost of termite Coptotermes curvignathus attack on buildings is enormous. In Indonesia, we know one environmental tolerant method to overcome the attack which is called baiting systems. However, this methods is relatively expensive, because there is only one product available all over the country. Chitosan is known for its bioactive ability as the retardant in mushrooms and fungi growth. Based on these facts, chitosan is assumed had the capability as a substance that could eradicate subterannean termite with baiting system which are environmental tolerant. Chitosan was dissolved in acetatic acid solvent. The concentration of the chitosan solvent used in this research were 0% (control), 0,25%, 0,5%, 1%, 2%, 3%, 4%, and 5%. The samples in this research were filter papers. The responses analyzed were percentage of termite mortality and weight loss percentages. Concentration of 0,5% chitosan gave significant affect on mortality of subterannean termite C. curvignathus. The highest percentage of mortality of subterannean termite C. curvignathus was by 4% concentration, which was 94,2%. While the weight loss percentage of filter papers gave a very significant affect at 1% concentration. The lowest weight loss percentage of filter papers was at 4% concentration of chitosan solvent, which was 7,4%.